ANALISIS TINGKAT KESEHATAN BANK DAN LUAS PENGUNGKAPAN PERISTIWA SETELAH TANGGAL NERACA PADA LAPORAN TAHUNAN PERBANKAN YANG TERDAFTAR DI BEJ - Juniati Gunawan; Purnama S. Dewi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
Banking and monetary policy play an important role in Indonesian economic development. Many people and organizations are using banking services to save their money or make loans. Therefore, the most important thing that must be done by bank is keeping people's trust to monetary system, through its close relationship with the coor-dinators and government institutions.To support the success of trustworthy and sound banking industrial develop-ment in Indonesia, it's needed a complete, accurate, and reliable information about many things of banking activities. Subsequent event disclosure is one of the most important information disclosure that should be disclosed in annual banking report, because it's very useful for an auditor to determine whether there're something material that will be able to influence valuation or appraising of financial statements are being audited.The aim of this paper is to analyze sound banking standard and disclosure level of subsequent event on annual banking reports which are listed in Jakarta Stock Exchange, in 31 December 2001.The research methodology that used is co-relational descriptive analyses by getting data from annual banking reports in Jakarta Stock Exchange library. The result is there are a positive correlation between sound banking standard and disclosure level of subsequent event. But its correlation is very weak because the score is only 0.25. Meanwhile, 6.37% score of R square shows that subsequent event disclosure is more influenced by another factors besides sound banking standard.Keywords: Sound banking standard, disclosure level, subsequent event, annual banking reports.